The Moderating Effect of Gamification on Loyalty Program Usage in Indonesian E-Commerce - Arta Moro Sundjaja; Giovanka Savina; Yuli Yuli; Thomas Hardianto (Bina Nusantara University, 2022)
Previously, existing research has not comprehensively examined the determinant factors of loyalty programs, and there is limited research that analyzes the gamification of loyalty programs in e-commerce. The research investigated the determinant factors of loyalty program usage, focusing on the moderating effect of the gamified loyalty program. The research applied a quantitative method using Structural Equation Modeling (SEM) with AMOS. Then, the unit of analysis was the users who played the Lucky Egg. The population size was unknown due to limited access to the e-commerce company, so the sample size was determined using ten times indicators. Around 242 respondents were gathered using convenience sampling. The result confirms that seven hypotheses are accepted, and one hypothesis is rejected. The determinant factors of loyalty program usage are playfulness, affective commitment, and attitude toward loyalty program. The interaction moderation analysis shows that the loyalty program increases loyalty program usage. However, the reward attractiveness does not affect the loyalty program directly and must be mediated by attitude toward the loyalty program. The R2 value of attitude toward loyalty program is 58,3%, and loyalty program usage is 58,5%. The research extends the loyalty program usage model in Indonesian e-commerce, and gamified loyalty program is proven as moderating variable of loyalty program usage.